Strategic Foresight: Scenario Planning For Sharia Joint Financing - Joice Fiskia Yusriani; Sahat Hutajulu (SEIKO : Journal of Management & Business, 2025)
Islamic financial institutions are required to face significant uncertainties in the process of establishing new Shariah-compliant businesses, particularly permissive contract structures and operating re-tooling requirements. In this environment, this study endeavors to bridge the current gap by developing a structured scenario planning method to aid strategic foresight related to launching a new product through an Islamic feature- Sharia joint financing facility at an Indonesian Islamic bank. This approach utilizes a qualitative interpretation format through stakeholder interviews and STEEP analysis to determine how driving forces are identified and prioritized. The findings underscore two critical uncertainties that most affect business outcomes in the future, namely the readiness and stability of the IT ecosystem and achievement of key business and financial metrics. These critical uncertainties construct four viable scenarios, for which the Strategy Diamond Framework is proposed as a facility describing strong strategic options. This study contributes a systematized approach to transform the notion of strategic foresight into concrete and operational roadmap in response to innovation challenges arisen from Islamic finance.